The state of circular economy implementation in the building and construction sector in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Environmental Management at Massey University, New Zealand - Cossar, Lucy (Massey University, 2024)
The building and construction (B&C) sector is pivotal in achieving a global shift towards a circular economy (CE) and moving away from a linear or 'take-make-dispose' model that drives unsustainable consumption rates and degrades vital ecosystem services. However, little is known about the extent to which B&C businesses implement the CE concept in Aotearoa New Zealand. Therefore, this study assessed the current level of implementation of the CE concept among businesses in Aotearoa New Zealand’s B&C sector. An exploratory sequential mixed-methods research design was utilised, beginning with the synthesis of circular strategies derived from existing literature. Experts representing seven business types (manufacturing, architecture and engineering, construction, design-build, fit-out, demolition, and waste management companies) were interviewed to explore the relevance of circular strategies, informing the development of a survey distributed to professionals from across Aotearoa New Zealand’s B&C sector. Most circular strategies were considered relevant by interviewees and were subsequently included in the survey. Interviewees also suggested that CE implementation is insufficient, inconsistent, uncoordinated, and limited by a narrow focus on recycling, necessitating more education, emphasis on the design phase, and a systemic and collaborative approach. According to the survey responses from 213 professionals, most businesses are at a ‘beginner’ stage of maturity regarding CE implementation, and most circular strategies receive minimal to moderate levels of implementation. Therefore, most circular strategies require greater attention, particularly service-based models, sharing platforms, material passports, remanufacturing, take-back schemes, organic recycling, and regenerating nature. These findings suggest that CE implementation among businesses in Aotearoa New Zealand's B&C sector is still in its early stages. In this context, there is significant potential to increase engagement in circular strategies, especially at the higher levels of the waste hierarchy and 9Rs, to accelerate the shift towards a more sustainable and circular economy.
Keywords: building and construction; circular economy; implementation; New Zealand; circular strategies; 330203 Building industry studies; 401106 Waste management, reduction, reuse and recycling